Privacy Law and Journalism in Nigeria: Knowledge, Uses and Challenges - Nyitse, Gabriel T.; Ogbu, Benjamin Ejuwa; Odeba, Ben (European Journal of Applied Sciences, 2023)
The mass media sector has been plagued by a number of privacy issues, some of which are attributed to media professionals and others to the advancement of digital media technology. This study looked into how Nigerian journalists understood, applied, and struggled with privacy law. The Communication Privacy Management Theory served as the study’s conceptual foundation. (CPMT). A mixed-methods research design was used for the study. (qualitative and quantitative). To working journalists in Abuja, Nigeria, a random sample of 30 interviews and 195 surveys were administered. The decision to base the capital of Nigeria in Abuja on its multiculturalism ensures that the city’s journalist population fairly represents all of Nigeria’s regions. The study’s key findings revealed that 95% of journalists have a thorough understanding of privacy law and apply it to their work as journalists. The 30 interviewee journalists all shared the same opinion. Everyone involved in the investigation agrees that implementing privacy laws will be extremely challenging and that the age of rapidly advancing high technology will only exacerbate the issue. The conclusion suggests that privacy concerns are more implementation-related due to the complexity associated with the development of digital media technology.